Solar Thermal Systems – Towards a Systematic Characterization of Building Integration. (June 2016) - Aelenei, Laura; Smyth, Mervyn; Platzer, Werner; Norton, Brian; Kennedy, David; Kalogirou, Soteris; Maurer, Christoph
Abstract: Characterization is defined as the act of describing distinctive characteristics or essential features. In most solar thermal collecting systems the energy performance characterization is commonly used as the most important criteria by which the system (or component) is represented. Building Integrated Solar Thermal Systems (BISTS) however are typically classified across a range of operating parameters, system features and mounting configurations, and other criteria are similarly important to be considered. Therefore BISTS characterization should also account for the architectural and building physics integration based on structural, functional and aesthetical features. A comprehensive characterization of BISTS is necessary to give designers, installers and end users confidence that the final solution selected is appropriate to the comprehensive building requirements.